Synthesis of Cu-Zn-Al shape memory alloy via electrodeposition on aluminum substrate - Almadrones, Emma Lorica (2010)
Shape memory alloys (SMAs) are unique smart materials characterized by their shape memory behavior of the ability to recover their shape prior to deformation upon heat treatment and their pseudoelasticity behavior or the non-linear elasticity capability of recovering from apparent plastic starins. The conventional methods of manufacturing this material are via conduction melting or powder metallurgy techniques. This study, however, successfully fabricated the ternary alloy of Cu-Zn-Al thru an alternative method, which is the electrodeposition-annealing route. The three main processes involved in this syntheses are (q) metal sustrate preparation, (b) electrodeposition and (c) thermal alloying. Thermal alloying, quenching treatment and bending were performed before si=ubjecting the alloyed to the flame test method to check for the shape memory behavior. Several SMA characterization techniques were carried out afterwards to further define and understand this unique behavior once affirmative response to the flame test was produced. The microstructure was analyzed using both an optical microscope and a combination of SEM-EDS analysis. The elemental compositional analysis of the alloyed strips was provided by X-Ray (XRF) examination while the presence of crystal structures of various phases was detected by X-Ray Diffraction (XRD) analysis. Calorimetry test thru the use of Differential Scanning Calorimetry (DSC) equipment was done to identify its austenite and martensic transformation temperatures and further validation was made by electrical resistivity (ER) measurements. Acceptable substrate pre-treatments and plating recipes that could produce adherent deposits suitable for alloying were obtaind in this study. The plating kinetics was significantly linear in terms of the variation of the amount of metal deposit with plating time at a constant current density level. Annealing produced interdiffusion which produced strips with very strong one-way SME, exhibiting displacements over 80%. The microstructure of the Cu-Zn-Al strips showed single and multi-phase regions as depicted by the color variations and grains contrast obtained by optiocal and SEM imaging, respectively. Compositional analysis of the alloyed strips proved the occurence of inter-atomic diffusion of the three metals, in which there is deviation of compositions on each probed layers. X-Ray diffractogram patterns detected numerous martensite variants with their corresponding crystallographic orientations such as M18R (128,0018, 1418, 107, 1010), binary phases such as Cu5Zn8 (210, 032), CuZn (104, 210), AlCu4 (330), Al4Cu9, AlCu3 (002), Al2Cu (004), AlCu (-605), and some retained crystal structures of Cu (200,220). The generated aistenite and martensite transformation temperatures by DSC test were observed at a range of 71.84°C to 105.64°C and 117.23°C to 332.86°C, respectively. However, ER measurements confirmed the existence of subzero transformation as their respective austenite and martensite peak range were observed at -167.23°C -4.29°C and -138.6° - 5.41°C. Compositional analysis of the fabricated strips revealed that thet are not yet homogenized, thus, there is a need for further annealing the samples. Despite this, the fabricated strips exhibited enough shape memory response such that their intended applications can still be attained.
Thesis (M.S. Material Science and Engineering)--University of the Philippines Diliman.
Keywords: SMAs (Shape memory alloys).